ANALISIS KOMPARATIF MODEL SPRINGATE DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2018 - Rachmawati, Yuni; SULBAHRI, RIFANI AKBAR (Catholic University Musi Charitas, 2020)
Food and Beverage Industries is strategic sector, seen from the largest increase in realization of the 5 other industrial sectors. The mushrooming of Food Companies and the collapse of several food industries was both a challenge and a threat for the industry. Nyonya Meneer, a herbal medicine factory which was successful in its time was declared bankrupt in August 2017. This supports the research objective of analyzing the possible bankruptcy of Food and Beverage companies listed on the Indonesia Stock Exchange in 2018 using the Springate Model and the Zmijewski Model. By using purposive sampling, obtained thirteen Food and Beverage companies listed on the Indonesia Stock Exchange in the 2018 period. Data collection techniques used were documentation and analyzed with quantitative and qualitative descriptive. According to the Zmijewski method calculation, only one company is predicted to go bankrupt, namely PSDN. Meanwhile, according to the Springate model there are 5 companies that are predicted to go bankrupt namely ALTO, INDF, PSDN, ROTI and SKBM. While the accuracy test shows that the Zmijewski model has a higher accuracy rate than the Springate Model which is 92.3%.